Blood gas and lactate analysis in nesting loggerhead (Caretta caretta) and green (Chelonia mydas) sea turtles from southeastern Florida, USA - Faye E. Giebink; Justin R. Perrault; Madison Toonder; Sarah E. Hirsch; Derek M. Aoki; Craig A. Harms; Charles J. Innis; Nicole I. Stacy (PLoS ONE, 2026)
High-energy demands and transition to a catabolic state pose physiological challenges for sea turtles during the nesting season. The objectives of this study were to assess venous blood gas analytes and lactate in loggerhead ( Caretta caretta ) and green turtles ( Chelonia mydas ) nesting in southeastern Florida to establish species-specific reference intervals, examine correlations between blood analytes, and investigate differences between species. For each species, the goal was to identify associations of analytes with morphometrics, nest deposition date, and, in loggerheads, duration of emergence from the water to blood sampling. The agreement of lactate concentrations between two point-of-care analyzers (i-STAT and Nova Lactate Plus) was also compared. In total, 49 loggerheads and 30 green turtles were sampled over portions of two nesting seasons. Reference intervals were established for clinically normal nesting turtles for each species. Partial pressure of oxygen was higher in loggerheads, while partial pressure of carbon dioxide and bicarbonate were higher in green turtles. In loggerheads, lactate positively correlated with curved carapace length, while pH declined and lactate increased across the nesting season, and there were no relationships between blood analytes and time from emergence to blood collection. No morphometric or seasonal trends were observed for green turtles. There was a strong association between lactate concentrations determined by i-STAT and Nova Lactate Plus, with the i-STAT yielding higher results. The mild trend toward relative lactic acidosis across portions of the nesting season in loggerheads suggests that physiological strategies to manage periods of high-energy utilization during nesting activities vary between species. These results provide insight into the variability of blood analyte data of two species of nesting sea turtles, allow for understanding physiological and metabolic changes during nesting, and provide relevance for clinical evaluations during health assessment studies, stranding response, and rehabilitation.